2014
DOI: 10.1080/15459624.2014.922687
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Unsuspecting Workers to Deadly Atmospheres in Below-ground Confined Spaces and Investigation of Related Whole-Air Sample Composition Using Adsorption Gas Chromatography

Abstract: Hazardous atmospheres in confined spaces may be obvious when a source of air contamination or oxygen (O2) deficiency is recognized. Such is often the case in general industry settings, especially with work processes which create hazardous atmospheres that may be anticipated. Hazards present in active sewers are also well recognized; but the possibility that O2 deficiency or high airborne contaminant concentrations may exist in new construction sewers or storm drains has been repeatedly ignored with deadly resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…A common characteristic of confined spaces is the boundary surface [2]. Hazardous atmospheres confined by boundary surfaces have resulted in many fatal accidents [2][3][4][5][6][7][8]. The boundary surfaces of subsurface structures in the infrastructure are typically made of concrete and steel.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A common characteristic of confined spaces is the boundary surface [2]. Hazardous atmospheres confined by boundary surfaces have resulted in many fatal accidents [2][3][4][5][6][7][8]. The boundary surfaces of subsurface structures in the infrastructure are typically made of concrete and steel.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the information and comments provided in the articles mentioned above [1][2][3][4][5][6][7][8]10,14] indicated that the desirable characteristics of the contaminant to be used in a study of ventilation induced by natural forces include: This study describes considerations involved in undertaking this challenge in a manner that produces a high confidence in the results and provides a stable platform for further study. Demands for establishing and maintaining control over the environment in which the study c occur, introduces further complications that are not often considered or discussed in technical articles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Several individual skills are important in reducing these risks, such as communication skills (to understand verbal instructions), mainly when personal protection equipment or a self-contained compressed air breathing apparatus are used under high environmental noise and poor visibility conditions; capacity to make decisions quickly and efficiently and to perform actions safely; physical capacity to do tasks that demand great physical strength, especially when exposed to excessive heat, moisture, or cold, or need to remain in an uneasy position for long periods of time. [3][4][5] It is estimated that 85% of accidents in a confined space could have been avoided had the risks related to a site or activity been designated by warning signs and protective barriers. Many serious accidents happen because internal procedures do not provide preventive control and/or because they fail to monitor unfavorable environmental conditions.…”
mentioning
confidence: 99%
“…Some conditions often related to death are a confined space not recognized or indicated as such, overreliance on smell and vision, underestimation of risks, low perception of risks, and errors during rescue by poorly trained teams. 3 Any properly qualified worker may work in confined spaces, but some health conditions can be triggered or aggravated during work in these environments, increasing the risk of accidents or causing death. In addition to being physically apt to perform their activities appropriately, individuals should be psychologically prepared to work under special conditions and be sufficiently educated to understand the specific qualifications needed for the task.…”
mentioning
confidence: 99%